Time-Dependent Probabilistic Seismic Hazard Analysis Using the Simulated Records, the Case of Tehran - Babak Hajimohammadi (Iranian Society of Structrual Engineering (ISSE), 2015)
Common attenuation equations are developed by seismic records which belong to earthquakes that have happened so far. Although there are many recorded data during last 50 years, it is not possible to consider all possible wave propagation paths, site types and fault rupture mechanisms inclassical attenuation relations. This fact becomes more serious in near field cases and a common shortcoming in most attenuation equations is their low accuracyin estimation of near field parameters.Many important cities of the world such as Tehran are located nearby some active faults. For example, the North Tehran Fault is such a closeseismic source to Tehran Metropolitanarea andcould be considered asa near field source. Therefore, it is necessary to evaluate near field effects in most of hazard analyses, risk management programs, structural designs, etc.In past, it was routine to use attenuation equations in hazard analyses. In this project for avoiding from insufficient performance of attenuation equations in near field, proposed simulation datum byZafarani, et al., (2012), were used directly in the hazard analysis without converting them into attenuation equations.Besides, time dependent hazard analysis (Non-PoissonianModel) was used to taking into account the probable seismic activity of the North Tehran Fault.